2017
DOI: 10.1111/cei.13074
|View full text |Cite
|
Sign up to set email alerts
|

T cell suppression in the bone marrow of visceral leishmaniasis patients: impact of parasite load

Abstract: Visceral leishmaniasis (VL) is a disseminated and lethal disease of reticulo-endothelial system caused by protozoan parasites Leishmania donovani and L. infantum, which are known to induce host T cell suppression. To understand the impact of parasite load on T cell function, the present was focused on parasite load with T cell function in bone marrow of 26 VL patients. We observed significant enrichment of forkhead box protein 3 (FoxP3) (P = 0·0003) and interleukin (IL)-10 FoxP3 regulatory T cells (T ) (P = 0·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In addition, regarding the regulatory CD4 T-cell response, Treg cells were found to accumulate in the bone marrow of symptomatic VL patients from India. These Treg lymphocytes expand in response to L. (L.) donovani antigens and produce IL-10, which inhibits the T-cell response (13,14). In agreement, the frequencies of CD4 + CD25 High and CD4 + Foxp3 + Treg cells were reduced in the peripheral blood mononuclear cell (PBMC) compartment of symptomatic subjects (15).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, regarding the regulatory CD4 T-cell response, Treg cells were found to accumulate in the bone marrow of symptomatic VL patients from India. These Treg lymphocytes expand in response to L. (L.) donovani antigens and produce IL-10, which inhibits the T-cell response (13,14). In agreement, the frequencies of CD4 + CD25 High and CD4 + Foxp3 + Treg cells were reduced in the peripheral blood mononuclear cell (PBMC) compartment of symptomatic subjects (15).…”
Section: Introductionmentioning
confidence: 81%
“…TNF-a is one of the main cytokines involved in protection against VL; however, at high levels, it can also cause tissue damage (38,39). On the other hand, the IFN-g-producing CD4 + T cells are considered one of the main functional cells during Leishmania infection (13,40). However, IFN-g promotes macrophage stimulation and inhibition of Th2 cells; thus, when its secretion increases, the patient immune response may be more effective against the parasite (35).…”
Section: Discussionmentioning
confidence: 99%
“…This fact points out that not only residual HIV, but also Leishmania can be contributing to the severely impaired thymic function in VL/HIV patients. Previous studies have shown that Leishmania can affect T-cell progenitors in the bone marrow and the thymic microenvironment (46)(47)(48), which may also favor the deficient thymic output under conditions of VL. Additionally, as previously described, the parasite potentiates the immune activation degree (5,49), mainly in R-VL/HIV cases (13), which in turn may lead to thymic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, some peptide pools induced a suppressive effect on IL-10 production. This anti-inflammatory cytokine has been involved in parasite persistence and disease establishment but also in controlling an excessive inflammatory response [15,18,90]. The immunomodulatory effect of some of our peptides may not be beneficial to the host, given the role of IL-10 in the regulation of exsessive IFN-γ responses [18].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%